Fear manufacture in the propaganda discourse image of terrorist ISIS «Daesh» via websites - عباس علاء الدين احمد (ALBAHITH ALALAMI, 2017)
This study aims to observe and analysis the propaganda discourse image for Daesh, and know how it marketing the fear due to symbols structure, and discover the straight meanings and hidden inspiration, with the ideology that the image presented. The study is descriptive and qualitative, and the method is analytic survey used semiotic approach. The most important results of the study refer to: - Daesh functioning the image in fear manufacture in all it components: the symbol of savageness, body language, color, clothes uniform and professionally shot. - The indicative meaning of fear promoted by Daesh based of the manufacturing «Holy», and that mean places non-touchable and non-insulted. - Daesh used in its propaganda image discourse all methods of violence for fear manufacture: direct, verbal and symbol violence.